Pengaruh Persepsi Harga dan Citra Merek terhadap Minat Beli Minyak Goreng Tropical pada Supermarket XYZ - Aulia Dewi Akhmalia; Arif Fadilla (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine and analyze the effect of price perception and brand image partially and simultaneously on buying interest in tropical cooking oil at supermarket xyz. In this study using a quantitative approach. Primary data was obtained through survey results by providing questionnaires distributed through google form by asking a number of questions regarding Price Perception, Brand Image, and Purchase Interest. The sample of this study was collected using the Slovin formula and an error rate of 5% with a total sample of 400 respondents. The analytical technique used in this research is the technique of scale-range analysis and path analysis with the help of the Secessive Interval (MSI) Method. Microsoft Excel computer program and SPSS application. There is a positive and significant correlation between price perceptions and buying interest. There is a positive and significant correlation between brand image and purchase intention. Perception of price and brand image have a simultaneous effect on buying interest. Keywords: Price Perception; Brand Image; Buying Interest.